2019
DOI: 10.1519/jsc.0000000000002627
|View full text |Cite
|
Sign up to set email alerts
|

Order Effects of Resistance and Stretching Exercises on Heart Rate Variability and Blood Pressure in Healthy Adults

Abstract: da Silva Araujo, G, Behm, DG, Monteiro, ER, de Melo Fiuza, AGF, Gomes, TM, Vianna, JM, Reis, MS, and da Silva Novaes, J. Order effects of resistance and stretching exercises on heart rate variability and blood pressure in healthy adults. J Strength Cond Res XX(X): 000-000, 2018-The purpose of this study was to compare the acute effect of different combinations and order of resistance exercise (RE) and stretching exercise (SE) on heart rate variability, systolic blood pressure (SBP), and diastolic blood pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 30 publications
4
20
0
Order By: Relevance
“…Senescent cells are involved in various physiological and pathological conditions, including tumor suppression, embryonic development, and tissue repair [ 104 ]. The senescent phenotype was described for postmitotic cells such as neurons [ 105 ], osteocytes [ 106 ], retinal cells [ 107 ], myofibrils [ 108 ] and cardiomyocytes [ 109 ].…”
Section: Impairment Of the Mechanisms For Maintaining Genome Stabimentioning
confidence: 99%
“…Senescent cells are involved in various physiological and pathological conditions, including tumor suppression, embryonic development, and tissue repair [ 104 ]. The senescent phenotype was described for postmitotic cells such as neurons [ 105 ], osteocytes [ 106 ], retinal cells [ 107 ], myofibrils [ 108 ] and cardiomyocytes [ 109 ].…”
Section: Impairment Of the Mechanisms For Maintaining Genome Stabimentioning
confidence: 99%
“…4 ). Previous studies have investigated the effect of the sequence of interventions in other health care fields, such as cardiac (heart rate and blood pressure) and training performance, and suggested that the order in which interventions are performed can influence the outcome [ 31 – 33 ]. Although no studies have investigated the effect of the sequence of interventions related to SMT, it is possible that, similarly to other health care fields, the order in which interventions and mitigators are performed can influence the frequency and/or severity of benign AEs post-SMT.…”
Section: Discussionmentioning
confidence: 99%
“…Araújo et al 36 examined the effects of a combination of SS and RT in a very similar study design and found controversial results. The authors did not verify the flexibility levels of participants, which may have influenced the results.…”
Section: Discussionmentioning
confidence: 99%
“…However, the increased sympathetic drive during exercise may demonstrate a health risk for hypertensive and cardiopathic subjects. In addition, the study cited 36 stating that the results were due to the fact that trained subjects were analyzed (outside the clinical setting) since it is known that trained subjects have a much faster recovery. In addition to not quantifying the intensity of the stretching, another serious methodological error was to perform stretching until only slight discomfort, unlike that performed in practice by health professionals in general.…”
Section: Discussionmentioning
confidence: 99%